A Study on Accident Theories and Application to Maritime Accidents - Awal, Zobair Ibn; Hasegawa, Kazuhiko (Procedia Engineering, 2017)
Maritime accidents, when taking place, often affect in large scale over the environment, society and economy. Many such accidents have occurred in the past century. In this study, it is observed that the traditional approach towards maritime safety, in general, is reactive. It indicates that accidents are unpredictable, and this is the most fundamental problem in safety science. In this connection, a review on some notable accident theories/models was conducted where the attributes of different accident theories/models were compared. The literature review suggests that over the years accident theories/models have been originated from different disciplines and the theories/models have been evolving with the changes in the society. The study reveals that maritime accidents take place in a complex socio-technical context. In such accidents, a single root cause may be traced back in the cause-effect chain, but it is not enough for preventing similar accidents in the future. The accident of Titanic (1912) and the accident of Costa Concordia (2012) justify this argument. Therefore, the paper discusses the development and usage of a new technique, such as Logic Programming Technique (LPT), for analyzing and understanding accidents. From an engineering point of view, the study concludes that accidents may be treated as a system control problem and modern innovative technologies like LPT may be further developed and utilized in this regard.